Computer control of batch process plant (software development) - Safian, Salehudin (1995)
Batch processes are more complex and often poorly understood than continuous processes due to their multiproduct character and the process coordination in time as well as in quantity. The availability of low cost computers places a powerful tool to monitor, control, and improved the batch processing plant production. This thesis reports on the development of the control tools by means of programming using the Turbo Pascal 6.0 and MATLAB Student Edition software. The tool developed using the MATLAB Student Edition software provide the capabilities to analysis the system transfer function by using the PIT) controller. The output is in the form of bode plot, root locus, nyquist chart, nichols chart and the steady state error response analysis. The optimums PID parameters obtain arc being expected to be implement on the computer control of batch process plant software based on the real-time Proportional, Integral and Derivative (PID) algorithms. The algorithm has been successful tested using the Non-interacting Liquid Level Control of Three lank System plant models transfer function.